Law and theology : classic questions and contemporary perspectives - Opderbeck, David W. (Minneapolis : Fortress Press, 2019)
Law and Theology offers the definitive account of the relationship between law and theology in the Christian tradition. Drawing on diverse biblical texts and classic authors from the early church to contemporary voices from the modern period, David W. Opderbeck examines key legal questions and controversial case studies from an interdisciplinary perspective, breaking new ground for legal scholars and theologians alike. As a law professor, practicing attorney, and theologian, Opderbeck writes as an insider from both disciplines. This unique look brings fresh insight for both fields in a context where questions of theology and law are especially relevant--and increasingly urgent. Going beyond the culture wars, Opderbeck brings these real-world cases to life, examining the ins and outs of the most important legal questions facing American civic and religious life. Scholars and students of law and theology will find this book to be required reading in and outside the legal and theological classrooms.
Includes bibliographical references and indexes.
Keywords: Christianity and law; Law (Theology); Natural law -- Religious aspects -- Christianity